Relationship between on-the-job training and work performance among academic staff in Faculty of Educational Studies at Universiti Putra Malaysia / Muhd Muzaffar lqbal Ismail - Ismail, Muhd Muzaffar lqbal (2014)
Research has found that employee training has been matter of concern and attention by many organizations and learning institutions in Malaysia. Hence, various training program implement to enhance employees' work performance. According to Treven (2008) state that training is a learning experience in that it seeks a relatively permanent change in an individual that will improve the ability to perform on the job. This study reports shows the relationship between on-the-job training and work performance among academic staff in Faculty of Educational Studies at Universiti Putra Malaysia. The studies have shown that academic staff is apprehensive about the types of training that relate to their work performance in their career. The theoretical framework for this study is based on conceptual framework. Two dimensions representing independent variables contribute to on-the-job training are coaching and internship. Meanwhile, dependent variables contribute to work performance represented by two dimensions that are quality of work and job knowledge. Data are gathered through study and questionnaire that distribute to among academic staff in Faculty of Educational Studies at Universiti Putra Malaysia. Findings from this study provided insights on effectiveness of training attended by academic staff towards their work performance.